The Informational Efficiency of Econometric Model Forecasts - Berger, Allen N.; Krane, Spencer D. (The Review of Economics and Statistics, 1985)
The informational efficiency of econometric model forecasts made by Data Resources, Incorporated and Chase Econometrics is evaluated. The criterion tested is an implication of the rational expectations hypothesis. Statistically significant serial correlations are found for several series of one-period forecast revisions, indicating rejection of the efficiency hypothesis. The use of these one-period revisions avoids some problems that have plagued previous tests that employed different efficiency criteria. Alternative explanations of the empirical results are suggested and analyzed.